Application of Electrical Resistivity Sounding in delineation of the Aquifer Transmissivity and Basement Structure at Igarra, Southwestern Nigeria - Chinyem, Felix Iwebunor; Ovwamuedo, Glory; Adeleke, Taofiq Adebowale (Iraqi Journal of Science, 2024)
Information on the aquifer transmissivity and basement structure of Igarra, southwestern Nigeria, is scarce. Thus, this study aimed to apply electrical resistivity sounding and drilled borehole information to determine the underlying bedrock structure (basement structure) and the aquifer transmissivity of Igarra. Twenty vertical electrical soundings (VES) were carried out along 4 established E-W traverses intending to intercept the fracture systems. The resistivity data acquired were curved matched, and iterated using Schlumberger O’ Neil software to obtain layer parameters. The layer parameters were evaluated to obtain the Dar-`Zarrouk parameters, which were used to determine the aquifer transmissivity. The resistivity-sounding result revealed four to six geoelectric layers that comprised topsoil, lateritic soil, weathered basement, fractured basement, partially fractured basement and fresh basement. The VES result revealed an undulating basement, with depths varying from 20.1 m to 53.8 m, suggesting evidence of fracturing and faulting within the basement. Correlation of the VES data and borehole log revealed that the weathered and the fractured basement constitute the aquifers, found between 2.4 – 53.8 m depths, and aquifer thickness ranged from 0.7 – 44.3 m. Analysis of the VES result showed an average computed transmissivity value of 18.48 m2/day. These values indicate that the basement is undulating with adequate groundwater-yielding materials (aquifer), capable of promoting adequate recharge potentials from precipitation.